2006
DOI: 10.1111/j.1742-1241.2005.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of fluoroscopy in the removal of tracheobronchial pin aspiration

Abstract: In this study, we investigated the role of fluoroscopy in the bronchoscopic removal of aspirated pins. Of 373 patients who underwent bronchoscopy for presumed tracheobronchial foreign body aspiration, 56 pin aspiration cases were selected and divided into two groups according to whether fluoroscopic guidance was required (group I) or not (group II). The localisation of foreign bodies, mortality and morbidity ratios and the duration of the procedures were investigated. Pin aspiration percentage was 15. Pins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Hasdiraz et al, Ucan et al and Kaptanoglu et al noted an increased prevalence of pin in the right bronchial tree, but Sersar et al, Yuksel et al, M. Hamad et al have reported an increased prevalence in left bronchial tree explained on the basis of narrow lumen of left bronchial apparatus leading to more suction pressure explained by Bernoulli theorem. 8,15,5,6,12,18,19 Our study also supports right predominance over left with (41.66%) in right bronchial tree compared to the left bronchial side in (30.55%). Thirty one foreign bodies were removed utilizing a Karl Storz rigid bronchoscope.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Hasdiraz et al, Ucan et al and Kaptanoglu et al noted an increased prevalence of pin in the right bronchial tree, but Sersar et al, Yuksel et al, M. Hamad et al have reported an increased prevalence in left bronchial tree explained on the basis of narrow lumen of left bronchial apparatus leading to more suction pressure explained by Bernoulli theorem. 8,15,5,6,12,18,19 Our study also supports right predominance over left with (41.66%) in right bronchial tree compared to the left bronchial side in (30.55%). Thirty one foreign bodies were removed utilizing a Karl Storz rigid bronchoscope.…”
Section: Discussionsupporting
confidence: 74%
“…11,12 The use of bronchoscope has dramatically reduced the need for more invasive procedure like thoracotomy. In this paper, we present a cross sectional observational study of 36 cases of pearl pin inhalations and analyzing the role of immediate preoperative X-rays with particular emphasis on difficulties and challenges faced during management using rigid bronchoscope.…”
Section: Introductionmentioning
confidence: 99%
“…RB is usually recommended to remove foreign bodies from the airways [14,15,16], though it is relatively difficult to perform. Although RB has been established as a safe, effective means for removing a tracheal foreign body, the equipment and technique are not available in all medical centers.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in our series, the pins were equally distributed between the two lungs. In regard to anatomy, one would expect a predisposition toward the right side, yet when sharp and thin foreign objects are concerned, it seems that equal distribution is the norm, as presented in other studies 5, 7, 8…”
Section: Discussionmentioning
confidence: 72%